Father’s Lifetime Socioeconomic Status, Small for Gestational Age Infants, and Infant Mortality: A Population-Based Study - Enstad, Samantha (Ethn Dis, 2019)
OBJECTIVE: To ascertain the association between father’s lifetime socioeconomic status (SES) and rates of small for gestational age (SGA, defined as weight for gestational age <10th percentile) and infant mortality (defined as <365 days). METHODS: The study sample was limited to the singleton births of African American (n=8,331), non-Latina White (n=18,200), and Latina (n=2,637) women. Stratified and multilevel, multivariable logistic regression analyses were conducted on the Illinois transgenerational dataset of infants (1989-1991) and their Chicago-born parents (1956-1976) with appended US census income data (n=29,168). The median family income of father’s census tract residence during childhood and parenthood were used to assess lifetime SES. RESULTS: Births (n=8,113) to fathers with a lifetime low SES had a SGA rate of 13.3% compared with 6.6% for those (n=10,329) born to fathers with a lifetime high SES, RR = 1.97 (1.79, 2.17). The infant mortality rate of births to fathers with a lifetime low SES exceeded that of infant mortality rate of births to fathers with a lifetime high SES: 13/1,000 vs 5/1,000, respectively; RR = 2.71 (1.94, 3.77). The adjusted (controlling for mother’s age, education, marital status, and race/ethnicity) OR of SGA for fathers with childhood, parenthood, and lifetime low (vs high) SES were 1.15 (1.01, 1.31), 1.13 (1.02, 1.26), and 1.19 (1.05, 1.34), respectively. The adjusted OR of infant mortality for births to fathers with childhood, parenthood, and lifetime low (vs high) SES were 1.14 (.78, 1.67), 1.40 (.90, 2.18), and 1.31 (.90, 1.92), respectively. CONCLUSIONS: Low paternal socioeconomic status is a previously unrecognized determinant of SGA birth regardless of mother’s demographic status.